2017
DOI: 10.1016/j.tra.2016.11.017
|View full text |Cite
|
Sign up to set email alerts
|

New walking and cycling infrastructure and modal shift in the UK: A quasi-experimental panel study

Abstract: Heavy dependency on car use leads to traffic congestion, pollution, and physical inactivity, which impose high direct and indirect costs on society. Promoting walking and cycling has been recognised as one of the means of mitigating such negative effects. Various approaches have been taken to enhance walking and cycling levels and to reduce the use of automobiles. This paper examines the effectiveness of infrastructure interventions in promoting walking and cycling for transport. Two related sets of panel data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 45 publications
0
56
0
Order By: Relevance
“…With reference to the above and having made an analysis of the solutions described in literature regarding sustainable transport systems in urban areas it is worth indicating the following concepts: car-free zones, low emission zones (LOZs) [26,27], congestion charging [28], electric vehicles (EVs), hydrogen vehicles (HVs), hybrid electric vehicles (HEVs), zero-emission vehicles (ZEVs) [29,30], bike-sharing [31,32], car-sharing, carpooling, Park&Ride, Bike&Ride, Kiss&Ride [33][34][35], bus rapid transit (BRT), dedicated lanes for buses [36,37], priority for buses [38] and trams, free fare public transport (FFPT) [39], paid parking zones [40], promotion of walking and cycling [41,42], powered two-wheelers (PTWs) [43], electric powered two-wheelers (ePTWs) [44], electric freight vehicles (EFVs), light electric freight vehicles (LEFVs) [45][46][47], cargo cycles [48,49], loading/unloading bays [50][51][52], cargo consolidation centers (CCCs) [53], freight consolidation centers (FCCs) [54,55], urban consolidation centers (UCCs) [56], underground logistics system (ULS) [57,58], cargo hitching [59,60], cargo drones [61,62], light rail transit (LRT), light rail system (LRS) [63][64]…”
Section: Literature Reviewmentioning
confidence: 99%
“…With reference to the above and having made an analysis of the solutions described in literature regarding sustainable transport systems in urban areas it is worth indicating the following concepts: car-free zones, low emission zones (LOZs) [26,27], congestion charging [28], electric vehicles (EVs), hydrogen vehicles (HVs), hybrid electric vehicles (HEVs), zero-emission vehicles (ZEVs) [29,30], bike-sharing [31,32], car-sharing, carpooling, Park&Ride, Bike&Ride, Kiss&Ride [33][34][35], bus rapid transit (BRT), dedicated lanes for buses [36,37], priority for buses [38] and trams, free fare public transport (FFPT) [39], paid parking zones [40], promotion of walking and cycling [41,42], powered two-wheelers (PTWs) [43], electric powered two-wheelers (ePTWs) [44], electric freight vehicles (EFVs), light electric freight vehicles (LEFVs) [45][46][47], cargo cycles [48,49], loading/unloading bays [50][51][52], cargo consolidation centers (CCCs) [53], freight consolidation centers (FCCs) [54,55], urban consolidation centers (UCCs) [56], underground logistics system (ULS) [57,58], cargo hitching [59,60], cargo drones [61,62], light rail transit (LRT), light rail system (LRS) [63][64]…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, it was noted that their conclusions are context specific, as Stockholm, where the study was performed, has a well-functioning public transport system. Evidence of the low cross-elasticity between car and bicycle use was also provided by Song et al [37], who investigated the modal shift resulting from bicycle infrastructure implementation in three cities in the UK using a quasi-experiment panel study. They found that about 20% of the respondents had switched from driving to active transport modes, but also that a similar percentage had done the inverse shift.…”
Section: Mode Choicementioning
confidence: 78%
“…Supportive infrastructure will be an important component of improving AT prevalence, but it should be noted that other approaches to intervention will also be required. A recent study in the UK found that infrastructure provision may be a necessary, but not sufficient, condition for encouraging modal shift 49 . Changing travel behaviours is a complex undertaking and a variety of supportive measures spanning environmental, economic, legal, social, cultural and educational approaches will likely be required.…”
Section: Discussionmentioning
confidence: 99%